Attractant properties of chemical constituents of the green macroalga Ulva and their response effects on the commercially important sea urchin Tripneustes gratilla - Bowker, Jenna (Department of Biological Sciences, 2015)
Interest in commercial sea urchin aquaculture is growing worldwide. This is because sea urchins have good quality roe which is a delicacy in many countries. Since the quality of sea urchin roe is dependent on what the sea urchin eats, increased research is being carried out to understand sea urchin feeding preferences. Feeding preference is related to the attractiveness/palatability of the feed, which is thought to be based on its chemical composition. Since an unpalatable feed will result in the poor quality of the organism, evaluating the palatability of sea urchin artificial feeds is important. In South Africa, the sea urchin Tripneustes gratilla has been selected for aquaculture due to its fast growth and high quality roe. Although it is a generalist herbivore, various studies have shown that T. gratilla has a significant preference for the macroalgae Ulva. The purpose of this study is to assess what chemicals contained in Ulva cause this preference. Chemosensory trials involving Ulva and its chemical constituents, as well as wounded Ulva and an artificial feed, were carried out using a Y-shaped maze. Results indicate that T. gratilla are not deterred by DMS or acrylic acid as literature suggests. Since previous studies showed that these two chemicals deter urchins, this study demonstrates that there are species-specific relationships to chemicals found in algal material. Results also indicate that T. gratilla are deterred by wounded Ulva, ulvan and ethanol, but cannot differentiate between these constituents when the constituents are compared against each other or ethanolic extract, fresh Ulva and feed. Since the sea urchins are not consistently deterred by wounded Ulva, ulvan and ethanol when compared with other constituents, this indicates that T. gratilla are not very selective in what they are attracted to or deterred from.